On Post-Soviet Language Policy and Language Planning (KULT_online, 2010)
The edited volume Linguistic Changes in Post-Communist Eastern Europe and Eurasia describes the current linguistic situations and developments in post-Soviet countries. The collected articles explore sociolinguistic issues in the Czech Republic, Poland, Russia, Ukraine, Belarus, Kazakhstan, Uzbekistan, Georgia and Bulgaria. The articles are related to one another in regard to not only the method of investigation (from public policies to language), but also the similar investigation results concerning the tendencies in language change and the determination of the direction of language policy. The collection is part of the series "East European Monographs" and is well integrated in that series due to the broad geographical selection of the languages.